Profiling learning approaches among Saudi postgraduate medical trainees: advancing education in the Vision 2030 era - AlOmar, Reem S.; AlShamlan, Nouf A. (Frontiers in Medicine, 2025)
IntroductionUnderstanding learning approaches among postgraduate clinical trainees is essential for shaping educational policies that align with Saudi Arabia’s Vision 2030 and its healthcare transformation agenda. This study examines the predominant learning approaches among Saudi postgraduate trainees and explores their implications for medical education reform and workforce development policies.MethodsA nationwide cross-sectional online survey was administered to 2,010 trainees using the Approaches and Study Skills Inventory for Students (ASSIST). Bivariate and multinomial regression analyses were conducted to assess associations between learning approaches and trainee characteristics.ResultsA total of 1,187 trainees responded (response rate: 59.05%). The most common learning approaches were strategic (39.98%) and deep (37.22%). Female trainees were more likely to adopt the deep approach (adjusted RRR = 1.51, 95% CI: 1.02–2.24), while a history of failing a promotion exam significantly predicted the adoption of a surface learning approach (adjusted RRR = 2.85, 95% CI: 1.44–5.61).DiscussionLearning approaches among postgraduate trainees varied by sex and academic experience, with policy-relevant implications. These findings highlight the need for personalized, competency-based educational frameworks that account for diverse learner profiles. Tailored pedagogical strategies, informed by these patterns, can enhance workforce preparedness, support equitable training opportunities, and inform healthcare education policy reforms aligned with Vision 2030.